Genome‐wide association study for feedlot average daily gain in Nellore cattle (Bos indicus). (20th February 2014) - Santana, M.H.A.; Utsunomiya, Y.T.; Neves, H.H.R.; Gomes, R.C.; Garcia, J.F.; Fukumasu, H.; Silva, S.L.; Leme, P.R.; Coutinho, L.L.; Eler, J.P.; Ferraz, J.B.S.
Summary The genome‐wide association study (GWAS) results are presented for average daily gain (ADG) in Nellore cattle. Phenotype of 720 male Bos indicus animals with information of ADG in feedlots and 354 147 single‐nucleotide polymorphisms (SNPs) obtained from a database added by information from Illumina Bovine HD (777 962 SNPs) and Illumina BovineSNP50 (54 609) by imputation were used. After quality control and imputation, 290 620 SNPs remained in the association analysis, using R package Genome‐wide Rapid Association using Mixed Model and Regression method GRAMMAR‐Gamma. A genomic region with six significant SNPs, at Bonferroni‐corrected significance, was found on chromosome 3. The most significant SNP (rs42518459, BTA3: 85849977, p = 9.49 × 10−8) explained 5.62% of the phenotypic variance and had the allele substitution effect of −0.269 kg/day. Important genes such as PDE4B, LEPR, CYP2J2 and FGGY are located near this region, which is overlapped by 12 quantitative trait locus (QTLs) described for several production traits. Other regions with markers with suggestive effects were identified in BTA6 and BTA10. This study showed regions with major effects on ADG in Bos indicus in feedlots. This information may be useful to increase the efficiency of selecting this trait and to understand the physiological processes involved in its regulation.